Governance in Universities: The Institutional Performance Measurement System (IPMS) - MERI, MOHAMED MERI KAMAL (Archives of Business Research, 2018)
The higher education sector continues to be influenced by the market, as well as the continued pressures of lower government funding, and the need of citizens for easy access to educational services, and even with increased competition from international institutions. All these are the factors that determine the success of higher education institutions, and force the institutions to adapt quickly in an environment that requires a steady stream of satisfying educational services.. Over the last decade, changes in funding and growing demands from students and donors have created a whole new model of higher education.This new trend has changed the way higher education institutions are run and operated, and the public's perception of them. Higher education institutions ,now, need to be managed more as public administrations or a business in the private sector. New models not largely dependent on public and government grants, but it is always based on accountability to the public and satisfy the needs of society. In some new model, higher education institutions must increasingly generate revenue, as does any private sector for profit corporation. Academics see universities as the engine of total progress. They transfer their intellectual productions to the institutions to meet the needs of society; University governance is making this progress. Here, University governance appears to be a necessary and precondition for deepening the independence of universities and institutions of higher education. This research shows the principles of this governance, methodology, models, comparisons between countries, and proposes a new model.